An Adaptive Qos Aware Routing with Energy Efficient Approach for Biomedical Wireless Sensor Networks - Jayasutha, D.; Kalaiarasan, C. (International Journal of Engineering and Technology, 2018)
Biomedical Wireless Sensor Networks (BWSNs) supports the advancement of new health careservices regarding patient monitoring for continuous assessment of patient health and medical diagnosis within affordable cost. On the other hand, dealing with medical data, BWSN should develop mechanisms to provide a high quality of service (QoS) level. As well, BWSN composed with the typical battery powered sensor nodes and these additional QoS mechanisms make extra energy consumption that significantly reduces the lifetime of the network. The network lifetimeis consequently significant feature to assure the needs of QoS.Since, to enhance the network lifetime and its capacity to provide the required QoS new schemes are essential for BWSN.Thus, in this paper, an adaptive QoS aware routing with energy efficient (AQSREE) approach has been proposed for BWMS to assure the QoS of various packets at the same time it minimize the energy consumption of the nodes thus prolonging the lifetime of the network. The proposed AQSREE differentiates the ordinary packets and emergency packet before transmitting in each queue of the node and also selects the optimal route to reach the sink node by considering the packet transmission time, energy level and the link load fulfill the QoS requirements. Additionally, the AQSREE adjusts the contention window size adeptly for energy efficiency with respect to the data rate and energy level. The simulation results show that the proposed AQSREE approach can effectively reduce the energy consumption by ensuring the QoS requirements of BWSN.Â Â